OPTIMALISASI PERAN ORANG TUA DALAM PEMBERIAN SEX EDUCATION UNTUK MENCAPAI INDONESIA EMAS 2045: LITERATURE REVIEW - Nurul Setyowati; Farhan Kurniawan (Universitas Negeri Malang, 2022)
AbstractIndonesia is expected to get a demographic dividend in 2045. Adolescents play a crucial role in these occasions. Adolescent's sexual behavior variations may affect the development of reproductive health issues and Indonesia's demographic dividend. To curtail this sexual behavior aberration, effective sex education needs to be provided. But there are still many issues with the sex education parents provide their adolescents. In order to meet the goals of